Presidential Decree-Law No. 201/2014 On Amending Some Provisions of the Income Tax Law Promulgated by Law No. 91/2005 - Egypt (2025)
Presidential Decree-Law No. 201 of 2014 on amending Some Provisions of the income tax law promulgated by law no. 91 of the year 2005 قرار رئيس جمهورية مصر العربية بالقانون رقم 201 لسنة 2014 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005